Arthroscopic “Crisscross” Fixation Technique for Avulsion Fracture of the Posterior Cruciate Ligament From the Tibia - Chirag Thonse, M.S.(Orth); Mohit Thapa Magar, M.S.(Orth); Dhruv Paul, M.S.(Orth) (Arthroscopy Techniques)
This study describes a method of fixing posterior cruciate ligament (PCL) avulsion fractures called the arthroscopic crisscross technique. PCL avulsion fracture is a rare injury that generally occurs in young patients. A displaced avulsion fracture at the tibial attachment of the PCL is an indication for surgical reduction and internal fixation given that nonunion, posterior instability, and early degenerative changes of the knee are common consequences of conservative treatment. This study describes all-arthroscopic fixation of the PCL avulsion injury using 2 No. 2 FiberTape sutures (nonabsorbable polyblend; Arthrex) via the arthroscopic crisscross technique. The No. 2 FiberTapes crisscross each other over the avulsed fragment. Through tensioning of both No. 2 FiberTapes, they are fixed anteriorly using a suture button. This technique can be considered a safe and effective method using minimal resources for the fixation of the avulsed PCL from its tibial footprint.